ARGO WISATA DALAM MEWUJUDKAN KEUNGGULAN BERSAING DESA DENGAN METODE PARTICIPATORY RURAL APPRAISAL (PRA) - Abdi Khairusy, Mirza; Prameswari, Yuda Nabella; Putra, Alfian Prayana Ardie; Ferial, Linardita; Atmaja, Sukarta (LPPM Universitas Bina Bangsa, 2025)
This community service activity aims to explore potential in efforts to realize sustainable development goals (SDGs) using the participatory rural appraisal (PRA) method in Pengawinan Village, Bandung District, Serang Regency, Banten Province. Ecotourism, heritage tourism, rural/farm tourism, and community tourism are steps that need to be developed to create a competitive tourist village. The involvement of each party in this program must work together so that the Bandung District area, especially Pengawinan Village, has an attraction at both local, national and international levels